The potential anti-cancer effects of melatonin on breast cancer - Naba Kumar Das; Saptadip Samanta (Open Exploration Publishing Inc., 2022)
Melatonin is the primary hormone of the pineal gland that is secreted at night. It regulates many physiological functions, including the sleep-wake cycle, gonadal activity, free radical scavenging, immunomodulation, neuro-protection, and cancer progression. The precise functions of melatonin are mediated by guanosine triphosphate (GTP)-binding protein (G-protein) coupled melatonin receptor 1 (MT1) and MT2 receptors. However, nuclear receptors are also associated with melatonin activity. Circadian rhythm disruption, shift work, and light exposure at night hamper melatonin production. Impaired melatonin level promotes various pathophysiological changes, including cancer. In our modern society, breast cancer is a serious problem throughout the world. Several studies have been indicated the link between low levels of melatonin and breast cancer development. Melatonin has oncostatic properties in breast cancer cells. This indolamine advances apoptosis, which arrests the cell cycle and regulates metabolic activity. Moreover, melatonin increases the treatment efficacy of cancer and can be used as an adjuvant with chemotherapeutic agents.